2020
DOI: 10.3390/en13143674
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thermal Environment in Pedestrian Space Using 3D Thermal Imaging

Abstract: Pedestrian space is an important place for people’s outdoor activities. Its thermal environment affects pedestrian walking experience, route selection and physical health. This study presents a 3D thermography-based method to analyze and evaluate the spatial distribution of thermal comfort. The proposed 3D thermal image was generated using 3D city models captured by an unmanned aerial vehicle (UAV) and thermal images gathered by an infrared camera. It can visualize construction elements, but also simply output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The drone quickly captured the entire territory. For high-quality drone scanning of public spaces, it is important to use a planned flight that guarantees full coverage of the area [9]. The planned flight will also be less time consuming compared to a comparable manual drone flight.…”
Section: Methodsmentioning
confidence: 99%
“…The drone quickly captured the entire territory. For high-quality drone scanning of public spaces, it is important to use a planned flight that guarantees full coverage of the area [9]. The planned flight will also be less time consuming compared to a comparable manual drone flight.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal imaging is commonly used to map the heatscape of street material, where issues of micro-scale urban heat islands, albedo, impacts of vegetation, and relative heat performance of different building compounds can be assessed by sensing. Work by Zhao et al [110], for example, introduced three-dimensional thermal imaging to assess the heat characteristics of different pedestrian spaces on streets. Other approaches use thermal sensing to identify pedestrians (by their temperature signatures) within thermal scenes [111], and a range of research has shown that heat sensing can be used to trace pedestrian movement outdoors.…”
Section: Sensorsmentioning
confidence: 99%
“…Thermal infrared technology converts the thermal infrared signals from ground objects into visually distinguishable images, and calculates temperature values to reflect the surface temperature distribution. At present, the surface temperature distribution map obtained by this technology is the most intuitive method commonly used in urban research to reflect the regional thermal environment (Wu et al, 2016;Zhao et al, 2020).…”
Section: Y Pan and T Zhangmentioning
confidence: 99%